A method for preparing composite phase change fiber
By blending radial spherical silica nanospheres with polyethylene glycol and blending with polyamide 6, composite phase change fibers are prepared, which solves the problem of difficult application of composite phase change materials in high-temperature polymer matrix. , high thermal stability and excellent phase transition performance are achieved.
Patent Information
- Application Number
- CN202310699066.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-14
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2043-06-14
AI Technical Summary
Existing composite phase change materials are difficult to use in polymer matrix with higher melt spinning temperatures, resulting in poor thermal stability and phase change performance.
Compound phase change fillers are prepared by blending radial spherical silica nanospheres with polyethylene glycol, and blending them with polyamide 6, and composite phase change fibers are prepared by melt spinning and thermal drafting techniques.
The thermal stability and phase change performance of the fiber are improved, the fracture strength and phase change enthalpy of the fiber are enhanced, and good thermal stability and temperature adjustment effect are achieved in high-temperature environments.
Smart Images

Figure CN116555937B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of phase change fiber preparation, and in particular to a method for preparing a composite phase change fiber. Background Art
[0002] For thousands of years, fibers and fabrics have been accompanying the development of mankind and have become a symbol of social civilization and progress. In recent years, with the advancement of science and technology, various functional fabrics have emerged in an endless stream. In addition to being used in civilian clothing materials to provide protection, warmth, and decoration for the human body, they are also widely used in aviation, construction, medical and health fields. The American smart thermal insulation jacket has attracted attention. It is made of a yarn that can expand and contract with temperature changes, thereby achieving intelligent temperature control and can be used in different seasons. Similar functional textiles have already occupied an important position in the market and have unique uses. This kind of fabric requires that the fiber not only has the basic properties of comfort, but also needs to be able to respond appropriately by sensing changes in the external environment.
[0003] Phase change thermoregulating fiber is a type of functional fiber that is developing rapidly. It uses the performance of phase change medium to respond to temperature changes to adjust the "microclimate" between the human body and clothing in high or low temperature environments, so that the human body is in a comfortable temperature environment. Phase change thermoregulating fiber was originally developed by NASA to improve the thermal performance of space suits and effectively cope with temperature fluctuations in outer space. The emergence of this technology has triggered more research and development of phase change thermoregulating fibers and phase change materials.
[0004] There are some problems that need to be solved in the process of preparing phase change thermostatic fibers by melt spinning. For example, most organic phase change materials with ideal performance have poor thermal stability, and are prone to solid-liquid phase change during the melt spinning process, resulting in loss of phase change performance. At the same time, they are prone to thermal decomposition under high temperature conditions. Therefore, the application of phase change materials with improved thermal stability to melt-spun phase change fibers has become a research hotspot.
[0005] At present, there are phase change fibers with a core-skin structure using a composite phase change material as the core layer and polypropylene as the skin layer, but the disadvantage is that the temperature adjustment range is higher than the comfortable temperature range required by the human body, and the breaking strength (1.35cN / dtex) is low, which is not conducive to subsequent clothing weaving. There is also a method of grafting the phase change material acrylic polyglycol ester onto a polypropylene matrix by reactive extrusion, and obtaining a PP-based phase change fiber by melt spinning. The experimental results show that the two have good compatibility, the fiber surface is uniform and smooth, the spinnability is good, and the enthalpy value reaches 6.93J / g. However, the phase change material contained in the above-mentioned type of fiber only meets the requirements of polypropylene melt spinning, and cannot be applied to polymer matrices with higher melt spinning temperatures, such as polyamide.
[0006] Blending is one of the most common fiber modification methods. Different functional fillers are added to the polymer matrix to give it different properties. Therefore, the current research focus is still on incorporating the synthesized composite phase change material with enhanced thermal stability as a functional filler into the polymer matrix, blending and granulating it, and then obtaining phase change temperature-regulating fibers through melt spinning. Summary of the invention
[0007] Based on this, the present invention provides a method for preparing a composite phase change fiber to solve the problem of applying existing composite phase change materials to a polymer matrix with a higher melt spinning temperature.
[0008] To achieve the above object, the present invention provides a method for preparing a composite phase change fiber, which comprises the following steps:
[0009] S1. Dissolve hexamethylenetetramine in deionized water, add hexadecyltrimethylammonium bromide, stir evenly, and obtain solution A; add tetraethyl orthosilicate and n-pentanol into cyclohexane, stir evenly, and obtain solution B; mix solution A and solution B and pour them into a hydrothermal reaction kettle, tighten the hydrothermal reaction kettle and put it into a constant temperature blast drying oven at 110-130° C. to react for 3-6 hours. After the reaction is completed, wait until the temperature of the hydrothermal reaction kettle drops to room temperature, open the kettle cover, take out the reaction product, wash it, vacuum dry it, collect the white solid product and grind it to obtain radial spherical silica nanospheres;
[0010] S2. Dispersing radial spherical silica nanospheres uniformly in anhydrous ethanol, adding polyethylene glycol and stirring to dissolve to obtain a suspension, performing rotary evaporation on a rotary evaporator to evaporate the anhydrous ethanol, and vacuum drying the remaining material after evaporation to obtain a composite phase change filler, wherein the mass fraction of polyethylene glycol in the composite phase change filler is 40 to 75%;
[0011] S3, blending polyamide 6 and a composite phase change filler according to a mass fraction of the composite phase change filler of 5 to 20%, and processing through a twin-screw extruder to obtain a phase change composite masterbatch (Q-SiO2@PEG);
[0012] S4. After drying the phase change composite masterbatch, spinning is performed through a melt spinning machine under sealed vacuum conditions to obtain composite phase change fibers.
[0013] As a further preferred technical solution of the present invention, in step S1, the dosage ratio of each component is: 0.2-1.0 g of hexamethylenetetramine, 20-40 mL of deionized water, 1.6-2.0 g of hexadecyltrimethylammonium bromide, 2.0-3.0 mL of tetraethyl orthosilicate, and 1.1-1.9 mL of n-pentanol.
[0014] As a further preferred technical solution of the present invention, in step S2, the molecular weight of the polyethylene glycol is 1500 g / mol.
[0015] As a further preferred technical solution of the present invention, in step S3, the polyamide 6 and the composite phase change filler are vacuum dried separately before being mixed.
[0016] As a further preferred technical solution of the present invention, in step S3, the blending temperature is 252-248°C.
[0017] As a further preferred technical solution of the present invention, in step S4, the melt spinning temperature is 245-273°C.
[0018] As a further preferred technical solution of the present invention, in step S4, the composite phase change fiber obtained by melt spinning is heat-stretched at a rate of 40 m / min, the stretching temperature is 60°C, and the heat-setting temperature is 90°C.
[0019] As a further preferred technical solution of the present invention, the draft ratio is 2.5 to 4.0.
[0020] According to another aspect of the present invention, the present invention further provides a composite phase change fiber, which is used as a phase change temperature regulating fabric.
[0021] The preparation method of the composite phase change fiber of the present invention uses Q-SiO2@PEG composite phase change filler as a functional phase change filler and polyamide 6 (PA6) as a polymer matrix, blends the two in different mass ratios, obtains functional masterbatch through twin-screw extrusion, and then uses a melt spinning machine to melt-spin it to obtain phase change fibers with different contents of functional fillers, and then performs heat drawing at different ratios to improve the stability of the fiber.
[0022] The present invention adopts the above technical solution to achieve the following beneficial effects:
[0023] 1) The composite phase change fiber of the present invention has ideal spinnability and good fiber-forming performance. From the surface and cross-sectional SEM images of the fiber, as the content of the composite phase change filler increases, the fiber surface becomes rougher. However, regardless of the content, the phase change functional filler is evenly dispersed in the phase change fiber without large-scale agglomeration. The surface micromorphology of the fiber is relatively uniform and intact, and the overall dispersion is good.
[0024] 2) The present invention has good uniformity of materials through twin-screw blending and granulation, and the composite phase-change filler is evenly distributed in the body with good dispersion, and no significant large-scale agglomeration occurs. This is mainly because the uniformity and dispersion of the materials are significantly improved after the twin-screw blending and granulation. On the other hand, the hydroxyl groups on the surface of radial spherical silica (Q-SiO2) nanospheres and polyethylene glycol (PEG) can form hydrogen bonds with the amide bonds in PA6, thereby improving the compatibility of the two. At the same time, the phase-change medium PEG loaded by Q-SiO2 as an organic phase also improves the compatibility of the two, thereby improving the spinnability of the material.
[0025] 3) After being stretched at different ratios, the fiber fineness, breaking strength and breaking elongation of the composite phase change fiber of the present invention all change regularly. With the increase of the stretching ratio, the breaking strength of the fiber gradually increases, and the breaking elongation gradually decreases. Moreover, with the increase of the stretching ratio, the degree of oriented crystallization of the fiber gradually increases, and the crystallization behavior gradually becomes complete.
[0026] 4) When the present invention adds composite phase change fillers of different mass fractions to the melt-spun composite phase change fiber, the phase change enthalpy values of the composite phase change fiber with mass fractions of 5%, 10%, 15%, and 20% are 2.31 J / g, 6.46 J / g, 12.28 J / g, and 17.53 J / g, respectively, which are not much different from the theoretical enthalpy value and have ideal phase change ability. The composite phase change fiber is woven into a fabric, and the temperature response time of the fabric in a hot and cold environment is tested using a hot and cold table. The results show that the fabric can provide a maximum temperature buffer time of 492s in a high temperature environment (70°C), and a heat preservation time of 121s in a low temperature environment (0°C), showing an excellent temperature regulation effect.
[0027] 5) The composite phase change fiber of the present invention was subjected to 50 hot and cold cycle tests. The results showed that before and after the cycle, the phase change enthalpy and phase change temperature of the fiber did not change significantly, showing good cycle stability and being able to maintain good thermal stability in a high temperature environment above 300°C. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments.
[0029] Figure 1 The (a) cooling and (b) heating DSC curves of the composite phase change fiber of Examples 1-4, where the percentages correspond to the mass fraction of polyethylene glycol in the composite phase change fiber.
[0030] Figure 2 The temperature rise curves of pure PA6 fiber and the phase change fiber of the present invention at (a) 70°C and (b) 0°C are shown.
[0031] Figure 3This is the DSC curve of the composite phase change fiber (PCF-15) of Example 3 after 50 cooling and heating cycles.
[0032] Figure 4 Infrared spectra of pure PA6, phase change filler Q-SiO2@PEG of Example 3, and phase change fiber PCF-15 of Example 3 before and after hot and cold cycles.
[0033] Figure 5 (a) TG curve and (b) DTG curve of pure PA6 and phase change fiber PCF-15 of Example 3.
[0034] The purpose, features and advantages of the present invention will be further described with reference to the accompanying drawings in conjunction with the embodiments. DETAILED DESCRIPTION
[0035] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.
[0036] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The test reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the experimental methods, unless otherwise specified, are all conventional methods.
[0037] The experimental reagents used in the following examples and comparative examples are shown in Table 1.
[0038] Table 1 Experimental reagents
[0039]
[0040] Example 1
[0041] This embodiment 1 provides a method for preparing a composite phase change fiber, which specifically includes the following steps:
[0042] Step S1, preparation of radially spherical silica (Q-SiO2) nanospheres with large pore size and high specific surface area, and preparation of Q-SiO2 by hydrothermal synthesis method.
[0043] (1) First, 0.6 g of alkaline catalyst hexamethylenetetramine (HMT) was dissolved in 30 mL of deionized water, and then 1.8 g of hexadecyltrimethylammonium bromide (CTAB) was added and stirred on a magnetic stirring table to obtain solution A.
[0044] (2) Then, 30 mL of cyclohexane was measured and poured into a beaker, and 2.5 mL of tetraethyl orthosilicate (TEOs) and 1.5 mL of n-pentanol were measured and added to the beaker using a pipette, and then stirred evenly on a magnetic stirring table to obtain solution B.
[0045] (3) Finally, pour solution B into solution A and continue stirring for 30 minutes; pour the stirred solution into the hydrothermal reactor, make sure the reactor is tightened and put into a 120°C constant temperature forced air drying oven for 4.5 hours. After the reaction is completed, open the lid of the reactor after the temperature of the reactor drops to room temperature and pour out the product. After washing with water and ethanol alternately for 6 times, vacuum dry it in a vacuum drying oven at 80°C for 12 hours, collect the white solid product and grind it to obtain radial spherical silica (Q-SiO2) nanospheres.
[0046] Step S2: using Q-SiO2 nanospheres as mesoporous carriers to prepare Q-SiO2@PEG composite phase change fillers.
[0047] The Q-SiO2 nanospheres were dispersed in anhydrous ethanol, and after being stirred evenly, polyethylene glycol was weighed and added thereto in an amount of 70% of the total weight of the Q-SiO2 nanospheres and polyethylene glycol, and the mixture was stirred and dispersed until completely dissolved, and then the obtained suspension was poured into a round-bottom flask, and rotary evaporated using a rotary evaporator, with the temperature set to 42°C. After the anhydrous ethanol in the round-bottom flask was almost completely evaporated, the sample in the flask was poured into a glass watch glass, and dried in a vacuum drying oven at 80°C for 12h to obtain a Q-SiO2@PEG composite phase change filler with a polyethylene glycol mass fraction of 70%.
[0048] Step S3, blending and granulation:
[0049] First, the polyamide 6 (PA6) slices were placed in a vacuum drum oven for drying. The program was set as follows: from room temperature to 90°C over 180 minutes, and then kept at 90°C for 900 minutes. After the end of the heat preservation, the temperature was raised to 110°C over 120 minutes and kept for 1080 minutes, and finally cooled to room temperature over 180 minutes. The Q-SiO2@PEG composite phase change filler was also dried in a vacuum oven at 60°C for 24 hours.
[0050] Next, the dried Q-SiO2@PEG and PA6 chips were blended in a mass ratio of 5 / 95, and then processed by a CTE20 PLUS twin-screw extruder to prepare PA6 / Q-SiO2@PEG composite masterbatch.
[0051] Step S3, melt spinning:
[0052] The composite masterbatch was placed in a 60°C vacuum drum oven for drying, and then the material was taken out and sealed, and spun on a C-type melt spinning machine. The primary fibers obtained by spinning were hot stretched at a rate of 40m / min, the stretching temperature was 60°C, the stretching ratio was 2.5, and the heat setting temperature was 90°C, and finally a composite phase change fiber (PFC) with a mass fraction of 5% of the composite phase change filler was obtained.
[0053] Embodiment 2-4
[0054] By using the preparation method and process compared with Example 1, only the blending mass ratio of Q-SiO2@PEG and PA6 slices was changed to 10 / 90, 15 / 85, and 20 / 80, respectively, and finally composite phase change fibers with a mass fraction of composite phase change filler of 10%, 15%, and 20% were obtained.
[0055] The performance test of the product of the above embodiment is as follows:
[0056] The fiber samples of Examples 1-4 were subjected to DSC tests of heating and cooling to obtain the thermal properties of different samples. Figure 1 The cooling and heating DSC curves of the composite phase change fiber are shown in Table 1. The corresponding thermal performance parameters are (with the Q-SiO2@PEG composite phase change filler of Implementation 1 as the comparison sample). It can be seen from the chart that the mass fraction of the composite phase change filler is 5%, 10%, 15%, and 20%, and the melting enthalpy of the composite phase change fiber is 2.31J / g, 6.46J / g, 12.28J / g, and 17.53J / g, respectively. With the increase of the content of the composite phase change filler, the thermal enthalpy value of the composite phase change fiber also gradually increases. Although there is a slight loss compared with the theoretical melting enthalpy value, the difference is not large. This shows that in the melt spinning process, the vacuum environment of the screw of the melt spinning machine can effectively prevent the thermal decomposition of the phase change material and retain the phase change properties of the material to a large extent. In addition, compared with the comparison sample, the crystallization temperature of the phase change fiber is significantly reduced. With the increase of the mass fraction of the composite phase change filler, the crystallization temperature gradually increases, showing a trend of gradually approaching the crystallization temperature of the composite phase change filler. The crystallization temperature and melting temperature of the composite phase change fiber with a mass fraction of 20% are closest to the composite phase change material, and it has the highest phase change enthalpy value. At the same time, the thermal enthalpy value of the composite phase change fiber with a mass fraction of 5% is also relatively ideal, both of which show excellent phase change performance.
[0057] Table 1 DSC data of phase change fibers
[0058]
[0059] The drawing ratio of spinning in Example 1-4 is 2.5, and the mass fraction of the obtained composite phase change filler is 5%, 10%, 15%, and 20%. The breaking strength and breaking elongation of the composite phase change fibers are 2.13 cN / dtex, 79.1%; 2.07 cN / dtex, 61.4%; 1.18 cN / dtex, 45.2%; 1.06 cN / dtex, 32.4% respectively; It can be seen that by comparing the breaking strength and breaking elongation of the composite phase change fibers with different composite phase change filler contents at the same drawing ratio, it can be found that with the increase of the mass fraction of the phase change filler, the breaking strength and breaking elongation of the composite phase change fibers both show a downward trend.
[0060] The response time of the composite phase change fiber under different temperature environments is the key to its heat storage and temperature regulation ability. The fibers obtained in Examples 1-4 were woven into a piece of fabric using a small loom, and the fabric made of pure polyamide 6 fiber was used as a control to test the response time of the fabric under different temperature cold and hot environments, and the cold-keeping time of the phase change fiber during the heating process and the heat-keeping time during the cooling process. The pure polyamide 6 fabric was named PA6, and the fiber fabrics of Examples 1-4 were named PFC-5, PFC-10, PFC-15, and PFC-20, respectively. Figure 2 The temperature-time curve of the fabric is shown. In the same high temperature environment, as the content of composite phase change filler in the fiber increases, the heating rate of the fabric gradually slows down, and a platform area appears near the phase change temperature (41°C), achieving temperature buffering. Compared with the fabric made of pure PA6, the temperature difference between the functional fabric and the pure PA6 fabric reaches the maximum when the temperature rises for 282s. The maximum temperature difference of the fabric with 20% phase change filler can reach 12.8°C, and the maximum temperature difference of the fabric with 15% phase change filler is as high as 9.4°C, both of which show obvious temperature regulation function. After the temperature buffer platform area, the temperature of the sample continues to rise to the ambient temperature and reaches equilibrium. During this process, the temperature regulation time of the fabric with 20% phase change filler is as long as 492s, and the temperature regulation time of the fabric with 15% phase change filler is 328s. The reason for this phenomenon is that when the phase change material in the fabric is heated to above the initial phase change temperature of PEG, PEG melts and absorbs heat, and at the same time delays the temperature rise. The above results all show that the fabric made of phase change composite fiber exhibits excellent temperature regulation effect.
[0061] During use, the cyclic stability of the composite phase change fiber is an extremely important parameter. Taking Example 3 as an example, the PCF-15 was subjected to fifty cold and hot cycle stability tests by DSC. Figure 3 (a) is the time curve of fifty hot and cold cycles, and (b) is the temperature curve. Analysis shows that there is basically no change before and after fifty cycles, and the curve remains consistent. The phase change temperature and phase change enthalpy of PCF-15 also remain stable without significant changes, indicating that the performance of PCF-15 has not changed after fifty cycles, and it has good cycle stability.
[0062] Next, infrared spectroscopy was performed on PCF-15 before and after the cycle test. Figure 4 As shown in the figure, before the hot and cold cycle test, PCF-15 was 3292cm -1 、1633cm -1 There are obvious characteristic peaks at 1540cm -1The absorption peak at 1095cm is formed by the coupling between CN stretching vibration and NH bending vibration, which are the characteristic peaks of PA6; -1 The absorption peak observed at is the asymmetric stretching vibration peak of Si-O-Si, indicating that Q-SiO2@PEG was observed in the spectrum of the phase change fiber. 70 In addition, compared with PA6 and Q-SiO2@PEG 70 , there is no new characteristic peak in the infrared spectrum of PCF-15, it is just a simple superposition of the absorption peaks of the first two, indicating that the composite of the polymer matrix and the phase change functional filler does not produce new chemical bonds, it is just a simple physical blending, and will not affect its chemical structure. Finally, the infrared spectra of the PCF-15 samples before and after the hot and cold cycle test were compared. The results showed that after 50 cycles, the chemical composition and structure of the phase change fiber did not change significantly, no absorption peak disappeared, and no new peak appeared, which further proved the chemical stability of the fiber in use.
[0063] Thermogravimetric analysis of PCF-15 samples was performed. Figure 5 The TG and DTG curves of pure PA6 and PCF-15 are shown in Figure 2. Figure 5 It can be seen that the thermal decomposition starting temperature of PCF-15 is lower than that of PA6. This is because the thermal decomposition temperature of the phase change medium in the phase change fiber is lower than that of PA6. During the heating process, the phase change medium first undergoes thermal decomposition, but the initial thermal decomposition temperature is 335.6°C, which is still maintained in a relatively high temperature area and has good heat resistance and stability.
[0064] Although specific embodiments of the present invention are described above, those skilled in the art should understand that these are merely examples and that various changes or modifications may be made to the embodiments without departing from the principles and essence of the present invention. The scope of protection of the present invention is limited only by the appended claims.
Claims
1. A method for preparing a composite phase change fiber, characterized in that: The following steps are involved: S1. Dissolve hexamethylenetetramine in deionized water, add hexadecyltrimethylammonium bromide, and stir evenly to obtain solution A; Add tetraethyl orthosilicate and n-pentanol to cyclohexane, stir evenly to obtain solution B; mix solution A and solution B and pour them into a hydrothermal reactor, tighten the hydrothermal reactor and put it into a 110-130 ℃ constant temperature forced air drying oven for reaction for 3-6 hours, after the reaction is completed, wait for the temperature of the hydrothermal reactor to drop to room temperature, open the reactor cover, take out the reaction product, wash it, vacuum dry it, collect the white solid product and grind it to obtain radial spherical silica nanospheres; S2, according to the amount of polyethylene glycol accounting for 40-75% of the total weight of the radial spherical silica nanospheres and the polyethylene glycol, adding the radial spherical silica nanospheres and the polyethylene glycol to anhydrous ethanol and stirring them evenly, rotary evaporating the obtained suspension using a rotary evaporator, and vacuum drying the remaining material after evaporation to obtain a composite phase change filler; S3, blending polyamide 6 and a composite phase change filler at a mass fraction of 5-20% of the composite phase change filler, and processing through a twin-screw extruder to obtain a phase change composite masterbatch; S4, drying the phase change composite masterbatch, and spinning it through a melt spinning machine under sealed vacuum conditions to obtain a composite phase change fiber; In step S4, the composite phase change fiber obtained by melt spinning is heat-stretched at a rate of 40 m / min, the stretching temperature is 60° C., and the heat setting temperature is 90° C.; the stretching ratio is 2.5-4.
0.
2. The method for preparing the composite phase change fiber according to claim 1, characterized in that: In step S1, the dosage ratio of each component is: 0.2-1.0 g of hexamethylenetetramine, 20-40 mL of deionized water, 1.6-2.0 g of hexadecyltrimethylammonium bromide, 2.0-3.0 mL of ethyl orthosilicate, and 1.1-1.9 mL of n-pentanol.
3. The method for preparing the composite phase change fiber according to claim 1, characterized in that: In step S2, the molecular weight of the polyethylene glycol is 1500 g / mol.
4. The method for preparing the composite phase change fiber according to claim 1, characterized in that: In step S3, the polyamide 6 and the composite phase change filler are vacuum dried before being mixed.
5. The method for preparing the composite phase change fiber according to claim 1, characterized in that: In step S3, the blending temperature is 252-248°C.
6. The method for preparing the composite phase change fiber according to claim 1, characterized in that: In step S4, the melt spinning temperature is 245-273°C.